2019
DOI: 10.1098/rstb.2018.0120
|View full text |Cite
|
Sign up to set email alerts
|

Variable DNA methylation in neonates mediates the association between prenatal smoking and birth weight

Abstract: There is great interest in the role epigenetic variation induced by non-genetic exposures may play in the context of health and disease. In particular, DNA methylation has previously been shown to be highly dynamic during the earliest stages of development and is influenced by in utero exposures such as maternal smoking and medication. In this study we sought to identify the specific DNA methylation differences in blood associated with prenatal and birth factors, including birth weight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 55 publications
5
42
0
Order By: Relevance
“…The results were consistent when restricted to births at term, demonstrating that the majority of our results were not driven by preterm births. We confirmed many of the findings from previously published EWAS of gestational age [23,26,27,29,30,67] and found a very high correlation between the significant CpG point estimates in previously published datasets compared to our study (e.g. corr = 0.92 between Hannon et al CpGs and our data; Additional file 1: Table S16), but importantly, we also found 3343 CpGs corresponding to 2577 genes that had not been described previously.…”
Section: Discussionsupporting
confidence: 93%
“…The results were consistent when restricted to births at term, demonstrating that the majority of our results were not driven by preterm births. We confirmed many of the findings from previously published EWAS of gestational age [23,26,27,29,30,67] and found a very high correlation between the significant CpG point estimates in previously published datasets compared to our study (e.g. corr = 0.92 between Hannon et al CpGs and our data; Additional file 1: Table S16), but importantly, we also found 3343 CpGs corresponding to 2577 genes that had not been described previously.…”
Section: Discussionsupporting
confidence: 93%
“…medications, stress, etc). The mean difference in DNA methylation between cases and controls for both psychosis and schizophrenia was small, consistent with other blood-based EWAS of schizophrenia 66 and complex traits [75][76][77] in general. While individually they may be too small to have a strong predictive power as a biomarker, together they may have utility as a molecular classifier 78 .…”
Section: Discussionsupporting
confidence: 87%
“…Relationships between smoking in the first trimester and lower maternal serum selenium levels at the end of the first trimester [12,27], as well as between maternal obesity/overweight and lower maternal selenium levels, were also found [12,27]. There is evidence of oxidative damage to lipids and proteins in smokers, and an increase in oxidative damage to DNA has been found in various biological materials [35]. DNA methylation that mediates between smoking and lower birth weight can also be a factor linking this unfavorable fetal outcome with adverse long-term health outcomes [35,36].…”
Section: Discussionmentioning
confidence: 77%
“…There is evidence of oxidative damage to lipids and proteins in smokers, and an increase in oxidative damage to DNA has been found in various biological materials [35]. DNA methylation that mediates between smoking and lower birth weight can also be a factor linking this unfavorable fetal outcome with adverse long-term health outcomes [35,36]. It should also be taken into account that smoking women may lead a different lifestyle that includes, for example, an unhealthy diet and other "unhealthy" behaviors [37].…”
Section: Discussionmentioning
confidence: 99%